Why does my shoulder hurt? A review of the neuroanatomical and biochemical basis of shoulder pain - Dean, B; Gwilym, S; Carr, A (2013)
If a patient asks 'why does my shoulder hurt?' the conversation will quickly turn to scientific theory and sometimes unsubstantiated conjecture. Frequently, the clinician becomes aware of the limits of the scientific basis of their explanation, demonstrating the incompleteness of our understanding of the nature of shoulder pain. This review takes a systematic approach to help answer fundamental questions relating to shoulder pain, with a view to providing insights into future research and novel methods for treating shoulder pain. We shall explore the roles of (1) the peripheral receptors, (2) peripheral pain processing or 'nociception', (3) the spinal cord, (4) the brain, (5) the location of receptors in the shoulder and (6) the neural anatomy of the shoulder. We also consider how these factors might contribute to the variability in the clinical presentation, the diagnosis and the treatment of shoulder pain. In this way we aim to provide an overview of the component parts of the peripheral pain detection system and central pain processing mechanisms in shoulder pain that interact to produce clinical pain.